Strawberry gingivitis as the first sign of wegener’s granulomatosis: a case report - Yongky Tamigoes; Riani Setiadhi (Journal of Dentomaxillofacial Science, 2019)
Objective: To describe that Wegenerâ€™s granulomatosis (WG) is an autoimÂmune multisystem disease with unknown etioloÂgy, characterized by the classic triad of necrotizing granulomas affecting the upper and lower respiratory tracts, disseminated vasculitis and glomerulonephritis. WG can affect any organ including kidneys, eyes or other organs. Oral involvement, like strawberry gingivitis, is an important sign of this disease even though it is rare.Methods: A 19 years old female was referred toÂ oral medicine clinicÂ with the chief complaint swelling on the gingiva which was increasing widespread. Since one month before the gingival enlargement did not respond to antibiotic. Â Intraoral examination, showed gingival enlargement at the upper anterior, palate, and first left mandibular molar. The swollen tissue was characterized by its granularity, short bulbous projections and bright red colour. The gingival appearance mimicking an overripe strawberry and extra oral examination showed cutaneous vasculitis at the hands and feet.Â  Laboratory evaluation presented erythrocyte sedimentation rate, CRP and eGFR (modified MORD) were elevated but the urinalysis was within normal ranges. Based on the anamnesis, clinical and laboratory examination,Â WGÂ diagnosis was made. The patient was treated with oral corticosteroids andÂ chlorhexidineÂ gluconateÂ 0.1%Â mouthwash.Results: The gingival inflammation improved after one month therapy andÂ the patientÂ still beingÂ followed-upÂ atÂ regulerÂ time.Â Conclusions: Early detection ofÂ oral manifestation of WG is importantÂ for dentists, especially oral medicine specialist, in orderÂ to achieve adequateÂ treatment and preventingÂ systemic tissue or organ damage.